Cross-species amplification of microsatellite loci developed for Passiflora edulis Sims. in related Passiflora Species - Oliveira,Gilmara Alvarenga Fachardo (2013)
The aim of this study was to evaluate the selected 41 SSR markers developed for yellow passion fruit (Passiflora edulis f. flavicarpa Sims.) for their transferability to 11 different Passiflora species. Twenty-one SSR were successfully amplified in 10 wild species of passion fruit producing 101 bands. All the markers were amplifiable for at least one species. The mean transferability was 68,8%, ranging from 15,4% (primer PE11) to 100 % (PE13, PE18, PE37, PE41 and PE88). Transferability was higher for the species from the Passiflora subgenus than for those from the Decaloba and Dysosmia subgenus. The results indicated a high level of nucleotide sequence conservation of the primer regions in the species evaluated, and consequently, they could potentially be used for the establishment of molecular strategies for use in passion fruit breeding and genetics.